The stieltjes transform of distributions - U. N. Tiwari; J. N. Pandey (International Journal of Mathematics and Mathematical Sciences)
In the present work, two complex inversion formulas of Byrne and Love for generalized Stieltjes transformation are shown to be valid for a class of distributions. This is accomplished by transfering the complex inversion formulas on the testing function space of a class of distributions and then showing that the limiting process in the resulting formula converges in the topology of the testing function space.